VALUE RELEVANCE OF TAX EXPENSE IN INDONESIA’S LQ45 COMPANIES - Aryo Bimo Setya Permana (Jurnal Penelitian Ekonomi Dan Akuntansi, 2025)
This study examines the value relevance of income tax information in the Indonesian capital market using firms listed in the LQ45 index from 2020 to 2024. Adopting the Feltham and Ohlson (1995) price valuation model, it includes book value, earnings per share (EPS), and tax expense as predictors of stock price. Ordinary Least Squares (OLS) regression results show all three variables significantly and positively affect stock price, with tax acting as an indicator of profitability. The findings underscore the strategic importance of transparent tax reporting in enhancing investor confidence, reducing information asymmetry, and improving the usefulness of financial statements.